PEMAHAMAN PEMILIHAN PEMINATAN AKADEMIK PESERTA DIDIK KELAS X SMAN 5 TANGERANG TAHUN 2017-2018 - Atik Nurlina (Universitas Sultan Ageng Tirtayasa, 2018)
This PTBK aims to improve the understanding of the selection of academic interests of new class X students through classical guidance services at SMAN 5 Tangerang in the academic year 2017-2018. Research on Selection of academic interest of learners held a week after the activity of acceptance of new learners (PPDB). The subjects of the study were all new students class X SMAN 5 Tangerang amounted to 340. Data collected through questionnaires, interviews and documentation. The hypothesis of classical counseling services can improve the understanding of learners in the selection of MIPA group academic and IPS group interests based on the ability, talent, interests, aspirations, and aspirations of parents.The results obtained data that classical guidance services can improve the understanding of the academic interests of new learners to select MIPA and IPS interest groups based on the ability, talents, interests, aspirations and aspirations of parents.Key Words: Elections, Academic Interest, Classical Guidance.